THE IMPORTANCE OF ENVIRONMENTALLY INNOVATIVE FABRICS IN COSTUME DESIGN EDUCATION (Conference Zone, 2022)
The life long environmental impact of the design industry and textile products is influenced by raw materials, their origin and product durability, in addition to production methods. At a general pace, it is natural for textiles to cause very surprising changes due to the use of raw materials and their impact on the environment, chemical, energy, water use, packaging and solid waste production, the appearance of unpleasant odors and noise pollution. This article will walk you through ideas and reflections on the importance of eco-innovative fabrics in costume design education.